Preliminary Checklist of Recent and Pleistocene Mollusca of Kentucky - David Bickel (Hello World!, 1967)
The Mollusca of Kentucky have been collected and studied since the early nineteenth century. Early workers, especially Rafinesque at Lexington, Kentucky and Thomas Say at New Harmony, Indiana, recognized Kentucky as a prime collecting ground. Throughout the nineteenth century mollusks from the state were studied by the country's malacologists, most of whom resided in larger eastern cities. These men accumulated their material occasionally by personal collecting, but more often by exchanging specimens with local naturalists or by hiring collectors.